Mach-IV: Evidence of Structural, Discriminant and Predictive Validity with Argentinian Students - Belaus, Anabel; Mola, Débora Jeanette; Correa, Pablo; Reyna, Cecilia (Revista de Psicología, 2022)
Machiavellians are defined as self-interested and manipulative people, who use others as mere means for their ends. The Mach-IV scale consists of 20 items measuring different aspects of Machiavellianism. In this study, we investigate the psychometric properties of the Mach-IV Scale with Argentinian university students. First, we translated and adapted the Mach-IV Scale to the target culture. Second, we evaluated the structure and internal consistency of the scale. Third, we examined the correlation between Mach-IV and Social Value Orientation (SVO), and between the Mach-IV scale and decisions and expectations in a Dictator Game (DG), both in its “give” and “take” versions. None of the structures evaluated showed good indexes of fit. We opted for the original one-factor structure but without items 19 and 20. Assuming such a structure, we observed negative correlations between the Mach-IV scale and SVO, and between the Mach-IV scale and cooperation in the DG. Materials, data, and scripts are available at https://bit.ly/2In6fgI.